Dopant-Free Hole Transporting Material Based on Nonconjugated Adamantane for High-Performance Perovskite Solar Cells - Fan, Dongyu; Zhang, Ren; Li, Yuheng; Shan, Chengwei; Li, Wenhui; Wang, Yunhao; Xu, Feiyang; Fan, Hua; Sun, Zonghao; Li, Xuehui; Zhao, Mengshuai; Kyaw, Aung Ko Ko; et al. (Frontiers in Chemistry, 2021)
A new dopant-free hole transporting material (HTM) 4',4''',4''''',4'''''''-(adamantane-1,3,5,7-tetrayl)tetrakis(N,N-bis(4-methoxyphenyl)-[1,1'-biphenyl]-4-amine) (Ad-Ph-OMeTAD) (named FDY for short), which consists of a non-conjugated 3D bulky caged adamantane (Ad) as core, triphenyl amines as side arms and phenyl units as linking bridge, is synthesized and applied in inverted planar perovskite solar cell (PSCs). As a result, the champion device with FDY as HTM yields an impressive power of conversion efficiency (PCE) of 18.69%, with JSC = 22.42 mA cm−2, VOC = 1.05 V, and FF = 79.31% under standard AM 1.5G illumination, which is ca. 20% higher than that of device based-on PEDOT:PSS (only 15.41%). Notably, the stability of PSC based-on FDY is much better than that of devices besed-on PEDOT:PSS, and the corresponding devices retain over 90% of their initial PCEs after storing for 60 days in nitrogen glove box without any encapsulation. Even storage in an open air condition with 50-60% relative humidity for 188 hours, the retained PCE is still over 81% of its initial one. All these results demonstrates that the new design strategy by combing the bulky and non-conjugated (aliphatic) adamantane unit as core and triphenyl amines as side arms can efficiently develop highly efficient HTMs for PSCs, which is different from the traditional way based-on conjugated backbones, and may open a new way for scientists to design small molecule HTMs for PSCs.